RANCANG BANGUN SISTEM PENGINGAT PENGGUNAAN MASKER DENGAN PENDETEKSI MASKER PADA WAJAH - Puput Oktarianti Saputri (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2022)
COVID-19 is the biggest health problem happening in the world today, this virus with its fast spread and strong resistance has claimed many lives. One way to prevent the spread of this virus quickly is to break the chain of its spread, and always comply with the COVID-19 Health protocol. Some examples of the COVID-19 Health Protocol are the use of masks, normal body temperature, always washing hands, and others. However, public awareness of compliance is still very low, so the COVID-19 pandemic has not ended until now. The best solution at this time is to monitor and ensure the use of COVID-19 Health protocols. However, with current technological advances and minimizing human contact, the author has designed a MASK USE REMINDER SYSTEM WITH MASK DETECTION ON THE FACE that uses machine learning technology to prevent human contact. With this tool, the author hopes to suppress the spread of COVID-19 and to end it so that all people can return to their normal activities without being disturbed by the virus.